Influência do uso de m-Health na adesão às práticas alimentares de profissionais de saúde: ensaio clínico randomizado - Stefanello, Fhaira Petter da Silva (2023)
Mobile app-based interventions seem to be effective for changing nutritional behaviors through food and nutrition education. Understanding food choices is essential to guide public policies and assertive nutritional interventions for a better quality of life of the population in the human aging process. Thus, the general objective of this study is to verify the influence of the use of m-Health in the adherence to food practices and changes in motivations for food choices. The specific objectives were: i) to verify the use of a mobile health application in the dietary practices of health professionals and ii) to analyze the use of a mobile application in the motivations for food choices of health professionals. The first scientific production presents the general and specific objective I. and the second scientific production presents the specific objective II. To answer the objectives of this thesis, a randomized clinical trial was conducted with 73 participants, health professionals aged between 20 and 59 years, of different genders, working in the public and private network. The sample was stratified into an intervention group (IG=36), which used the m-health technology for 3 months, and a control group (CG=37), which did not use the m-health technology. The instruments used were: a questionnaire with sociodemographic data, a Food Practices Scale to assess eating practices, The Eating Motivation Survey (TEMS) scale to assess motivations to eat, and the m-health technology used was an application called App Guia Alimentar (Food Guide App), based on the Food Guide for the Brazilian Population, for food and nutrition education. The meetings took place in person, for the completion of the questionnaires (pre and post intervention) and training in the use of the application. The results of the intervention indicate that m-health technology can improve some dietary practices and motivations to eat. The food practices in both groups were significantly different (p<0.001), with a mean score of 38.14 in the CG and 46.53 in the GI after the intervention; this result allows the identification of improvement in the score of food practices, especially in the intervention group. When we evaluated the motivations to eat, we found significant post-intervention differences in reasons such as habits, preference, price, and social image, which had lower means, and increased means for natural issues, socialization, and weight control. The empirical studies contribute to help direct public policies to promote healthy eating and lifestyle in aging humans through m-Health applications